A Study of Blood Transfusion Services before and during the COVID-19 Pandemic in a Tertiary Care Hospital (Pulse, 2025)
Background: The primary goal of safe blood transfusion services is to ensure continuous and easy access to blood components. However, during the COVID-19 pandemic, there was a sudden interruption at all levels of healthcare. The widespread transmission of the coronavirus prompted the government of Bangladesh to implement a nationwide lockdown.In this article, we have compared the blood transfusion services provided in the year 2019 with the impact of the COVID-19 pandemic on these services in 2020, focusing particularly on blood collection and supply. The aim was to assess the impact of the COVID-19 pandemic on blood transfusion services.Methodology: This retrospective study was conducted in the Department of Transfusion Medicine and Clinical Haematology at BIRDEM, Dhaka. The study assessed blood collection from donors and the supply of blood components to recipients retrospectively from January 2019 to December 2020. Data were collected from record registers, and analyzed as percentages and proportions.Results: In 2019, a total of 12,296 blood units were collected, whereas in 2020, the number dropped to 9,713. The overall supply of blood components in 2019 was 13,582, but this decreased to 9,486 in 2020. There was a reduction of 27.5% in the supply of blood components and a 21% decrease in the collection of blood from donors. Notably, there was a significant decline observed in both the collection and supply of blood during April and May of 2020. Conclusion: During the COVID-19 pandemic, there was a detrimental effect on blood supply and collection, which negatively impacted blood transfusion services. A suitable national guideline with a flexible blood transfusion policy can help address challenges related to safe blood transfusion services during the pandemic.Pulse Volume 16, Issue 2 2024, P: 13-18